Influence of B addition on the Mo diffusion-controlled eutectic dissolution process during homogenization of super austenitic stainless steel S31254 - Huanyu Tan; Jinyao Ma; Shucai Zhang; Huabing Li; Jiayu Wang; Liuwei Zheng; Peide Han (Journal of Materials Research and Technology, 2023)
The influence of B addition on dissolution behavior of (σ + γ)e eutectics of a 6Mo super austenitic stainless steel S31254 during the homogenization process was investigated by SEM-BSE observations combined with EDS. The results showed that the addition of 0.005 wt% B accelerated the dissolution of the σ phase controlled by Mo diffusion, during homogenization from 30 to 90 min at 1180 °C. TOF-SIMS results showed that B segregated along the σ/γ interface in the as-cast samples. TEM observations combined with EDS investigated the phase interfaces in two as-cast samples in detail to correlate σ phase dissolution. Compared with the B-free sample, the wide transition zone (∼60 nm) with a composition gradient was more clearly observed at the σ/γ interface in the B-containing sample. The transition zone with B had two features: local segregation of B element and precipitation of R phases at the σ/γ interface. R phases owned larger contents of Mo, which was not almost observed in the as-cast S31254. The results indicated that B segregation changed the phase interface, accelerating Mo diffusion at the σ/γ interface. In addition, the results of nanoindentation indicated a more uniform distribution of hardness at the σ/γ interface after homogenization of the B-containing sample, which can be beneficial to improve the deformation compatibility of S31254 during hot working.